Ectopic Mature Cerebral Tissue in the Nasal Cavity Incidentally Detected by 18F-FDG PET/CT. (January 2015) - Lococo, Filippo; Treglia, Giorgio; Filice, Angelina; Pernice, Carmine; Versari, Annibale; Paci, Massimiliano; Rapicetta, Cristian; Sgarbi, Giorgio
Abstract : Abstract: Herein we describe a rare case of neuroglial heterotopia (ectopic mature cerebral tissue) incidentally detected by 18 F-FDG PET/CT. A 52-year-old female patient underwent 18 F-FDG PET/CT for metabolic characterization of a left pulmonary nodule. 18 F-FDG PET/CT revealed increased radiopharmaceutical uptake corresponding to the pulmonary nodule pathologically described as adenocarcinoma. Furthermore, an area of increased 18 F-FDG uptake corresponding to a lesion in the left nasal cavity was detected. Endoscopic biopsy of the nasal lesion showed the presence of ectopic mature cerebral tissue suggesting the presence of neuroglial heterotopia.